Advancements in Design, Modelling, and Analysis of MEMS Vibrating Ring Gyroscopes for Harsh Environments - Gill, Waqas Amin (Curtin University, 2023)
This Ph.D. thesis presents the design and modeling analysis of microelectromechanical systems (MEMS) vibrating ring gyroscopes for harsh environments. The design analysis covers the dynamic study of the vibrating ring and semicircular support springs. Further, the mechanical, electrical, and damping effects of the MEMS vibrating ring gyroscope analyzed for external and internal ring gyroscopes. This thesis emphasizes the effects of temperature fluctuations and mode mismatch on the performance of two internal ring designs.